Principles of punishment without deprivation of liberty in the provisions of Vietnamese law - Thuy Lien , Tran (South Asian Journal of Social Sciences and Humanities, 2023)
Vietnam has promulgated many legal documents as a basis for the organization and operation of criminal judgment enforcement. However, most of them focus mainly on the execution of prison and death penalty without really paying enough attention to the execution of punishments without deprivation of liberty. The system of legal documents on penalty enforcement without deprivation of liberty was issued at different times, so there are still many shortcomings, many contents have not been specified, leading to many difficulties and obstacles in law enforcement. Because it is an administrative-judicial activity, the execution of punishments does not deprive freedom of many subjects, and the order and procedures for judgment execution are relatively complicated, errors may occur, reducing the sense of justice. The meaning of punishment is not deprivation of liberty. Therefore, studying the principles of punishment without deprivation of liberty in the provisions of the law has scientific and practical significance.
Keywords: Principle; punishment; not deprived of liberty; law; Vietnam